The Commercialization of Traditional Subsistence Hunting Activities in Bario, the Kelabit Highlands, Sarawak, Malaysian Borneo - Akbari, Akram (Curtin University, 2016)
This study creates a new framework identifying factors driving the commercialization of hunting in the Bario region of the Kelabit Highlands, Malaysian Borneo. It aims to assist the local hunters, communities and the Malaysian government to make more informed decisions regarding the impact of hunting on area biodiversity. Findings indicate that besides several categories of hunters in the region, bushmeat price impacts both the species hunted and consumers in and outside of the Highlands